2016
DOI: 10.1016/j.etp.2016.01.003
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo effects of lutein against cisplatin-induced ototoxicity

Abstract: Esta es la versión de autor del artículo publicado en: This is an author produced version of a paper published in: Experimental and Toxicologic Pathology 68.4 (2016): 197-204 A B S T R A C TIntroduction: Cisplatin is a commonly prescribed drug that produces ototoxicity as a side effect. Lutein is a carotenoid with antioxidant and anti-inflammatory properties previously tested for eye, heart and skin diseases but not evaluated to date in ear diseases.Aim: To evaluate the protective effects of lutein on HEI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 34 publications
(34 reference statements)
0
13
0
Order By: Relevance
“…A variety of antioxidants have been shown to reduce cisplatin-induced ototoxicity in animal models (Rybak et al 1999 ; Lopez-Gonzalez et al 2000 ; Choe et al 2004 ). Studies that show antioxidants protects against hair cell death in vitro (Kim et al 2014 ; Astolfi et al 2008 , Roldán-Fidalgo et al 2016 , reviewed in Sheth et al 2017 ) suggest that antioxidant-mediated protection can function downstream of cisplatin entry into the inner ear, since in vitro preparations eliminate the blood-labyrinth barrier and allow cisplatin to directly access hair cells. However, to date no studies have shown that antioxidants reduce cisplatin-induced hearing loss in humans.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of antioxidants have been shown to reduce cisplatin-induced ototoxicity in animal models (Rybak et al 1999 ; Lopez-Gonzalez et al 2000 ; Choe et al 2004 ). Studies that show antioxidants protects against hair cell death in vitro (Kim et al 2014 ; Astolfi et al 2008 , Roldán-Fidalgo et al 2016 , reviewed in Sheth et al 2017 ) suggest that antioxidant-mediated protection can function downstream of cisplatin entry into the inner ear, since in vitro preparations eliminate the blood-labyrinth barrier and allow cisplatin to directly access hair cells. However, to date no studies have shown that antioxidants reduce cisplatin-induced hearing loss in humans.…”
Section: Discussionmentioning
confidence: 99%
“…The cell lines and the cochlear explants indicated low toxicity for paromomycin, similar to that of apramycin, while the in-vivo studies demonstrated that it was clearly ototoxic, and comparable to neomycin and GM. Divergent data from in-vitro and in-vivo ototoxicity models have been recorded previously 53,54 . These might be related to the presence of vulnerable cell types in-vivo that have a role in the overall response to treatment and that are not present in in-vitro models, or to differential differentiation stages and signalling pathways being activated in the in-vitro versus in-vivo models 25,5557 .…”
Section: Discussionmentioning
confidence: 99%
“…Twenty rats received single intraperitoneal injection of Cisplatin drug (Hospira, UK Limited, Warwickshire) (10 mg/kg) each ( 17 ) and considered as positive control.…”
Section: Methodsmentioning
confidence: 99%